2023
DOI: 10.1039/d3ra01300f
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric and spectroscopic analyses along with the kinetic modeling of the pyrolysis of phosphate tailings

Abstract: Load the phosphorus tailings sample into a pyrolysis tube, heat it at different heating rates to 1000 °C, and calcine the sample at different temperatures in a muffle furnace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Phosphate ore flotation will produce a large amount of phosphate tailings. It is reported that for every 1t of phosphate concentrate produced, 0.44t of phosphate tailings will be generated [4]. At present, the utilization of phosphate tailings is mainly focused on pit filling [5], phosphate tailings re-election [6], construction material preparation [7,8], fertilizer production and other uses, with an overall utilization rate of less than 10% [9].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate ore flotation will produce a large amount of phosphate tailings. It is reported that for every 1t of phosphate concentrate produced, 0.44t of phosphate tailings will be generated [4]. At present, the utilization of phosphate tailings is mainly focused on pit filling [5], phosphate tailings re-election [6], construction material preparation [7,8], fertilizer production and other uses, with an overall utilization rate of less than 10% [9].…”
Section: Introductionmentioning
confidence: 99%